New world direct-developing frogs :phylogenetic relationships and biogeographic history (2018)
The overarching goal of this dissertation to show some patterns and processes involved in the diversification of the New World direct-developing frogs. Extant biodiversity is the result of the interplay between the historical processes of diversification, dispersal (or range shifts), and extinction, understanding mechanisms that drive these processes is essential in evolutionary biology. The lineage-specific phylogenetic baggage of species impinges particularities or trends that may ultimately affect their survival, extinction, and diversification. Moreover, the most important mechanisms generating and maintaining species diversity vary depending on the taxonomic, spatial and temporal scale over which they are quantified. The spatial mechanism could be understood at regional scales, the variation in the timing and rate of lineage diversification, and ecological factors, including the current and past expanse of suitable habitat. Whereas at local scales, biotic interactions and trait evolution in community assembly appear to be the most influential. Another way to assess the mechanism underlying the diversification process is by recognizing their characteristics, both intrinsic, e.g., body size, morphological adaptations, or genomic features, and extrinsic, e.g., microhabitat, environmental variation, or range size, both factors play a role in the survival or extinction of the lineage members and are required to understand extant diversity, the diversification process and its current distribution. Our aim is to explore the systematics, biogeography, and phlylogeography at different taxonomic levels of one of the most diverse groups of tetrapods: New World direct-developing frogs